Studi Komparasi Hasil Belajar Siswa Antara Model Cooperative Learning Tipe Team Game Tournament (TGT) Dengan Jigsaw Pada Pembelajaran Tematik Di Kelas IV SD Negeri 01 Kota Bengkulu - Mardeo Kurnaiawan; Sri Dadi; Pebrian Tarmizi (Universitas Bengkulu, 2020)
This Study purpose to determine the the most effective student learning outcomes between the cooperative learning type Team Game Tournament (TGT) model with type Jigsaw in thematic learning in class IV SD Negeri 01 Bengkulu City. The research method used was a quantitative design with the matching only pretest-posttest control group design. In this study the population was SD Negeri 01 Bengkulu City. The sampling technique used cluster random sampling with class IV B totaling 28 students as the experimental class I and class IV A totaling 26 as the experimental class II. The instruments used in this study were the test sheet and observation sheet. Data collection techniques in the form of tests and observations. Trial The data analysis technique used is quantitative analysis. Based on the results of hypothesis testing using the t-test, it is concluded that on student learning outcomes, the Cooperative Learning Type Team Game Torunament (TGT) model is more effective than Jigsaw in thematic learning in class IV SD Negeri 01 Bengkulu City.Keywords: Cooperative Leraning Model, Team Game Tournament Model, Jigsaw Model, Learning Outcomes, thematic learning